Ten years of progress in GW/P body research - Chan, Edward K. L.; Fritzler, Marvin J. (Advances in experimental medicine and biology, 2013)
GW bodies are novel cytoplasmic foci that were discovered and named by Dr. Chan’s group in 2002. These bodies are now known to be active cytoplasmic foci involved with the new gene regulation process mediated by microRNA that leads to translational repression and mRNA degradation. The detailed biological functions of these cytoplasmic structures are still being uncovered and the idea for this book is to provide the history of the discovery and the major work from different laboratories that has led to the characterization and elucidation of the structure and function of these new multiple subcellular structures